SOUND “L” CORRECTION FOR 5 – 6 YEARS OLD CHILDREN WITH INSUFFICIENT LANGUAGE SYSTEM DEVELOPMENT - Barkane, Evita (Education Reform: Education Content Research and Implementation Problems, 2019)
Work aim theoretical research of cognitions about sound “L” correction for 5 – 6 years old children, collect, make and recognise methodological material of sound “L” correction for childern with insufficient language system development at III level. Was Selected and analyzed literature about sound “L” correction among 5 – 6 years old children, about speech therapist work, about child’s language and speech development, was found out sound “L” pronouncation correction options for children with insufficient language system development at III level. Part was made questionnaire for speech therapists, to justify master’s work relevance. Author made situation research, made correction work, handle mathematically gained research data.Work author designed and recognised speech therapist methodical material about sound “L” correction for children with insufficient language system development at III level. Based on theoretical and research part scientific cognitions, was made speech therapist methodical material “Sound “L” pronouncation correction for 5 – 6 years old children with insufficient language system development at III level”. Methods used in the study: analysis of scientific literature; analysis of documents; questionnaire; observation; operational study; processing of statistical data; method of expert opinion.